Application of DEA on evaluating agricultural comprehensive productivity - CHEN Li-neng; XIE Yong-liang (浙江大学学报. 农业与生命科学版, 2000)
The paper given an analysis of the connotation, components and forming mechanism of agricultural comprehensive production capacity (ACPC), and showed the complexity of its evaluating method. After pointing out the shortcoming of present evaluating methods, regional ACPC efficiencies of the same term are measured and compared with DEA method. By using DEA efficiency as a clustering standard and looking for DEA effective units step by step, regional ACPC are clustered in different efficiency levels. The method above in evaluating the ACPC efficiencies of all regions in Zhejiang province of 1995 has been applied, and the results could provide scientific basis for the Zhejiang provincial and regional government to improve ACPC.